Failure of Supervised Chloroquine and Primaquine Regimen for the Treatment of Plasmodium vivax in the Peruvian Amazon - Graf, Paul C. F. (Hindawi Publishing Corporation, 2012)
The widespread use of primaquine (PQ) and chloroquine (CQ), together, may be responsible for the relatively few, isolated cases of chloroquine-resistant P. vivax (CQRPV) that have been reported from South America. We report here a case of P. vivax from the Amazon Basin of Peru that recurred against normally therapeutic blood levels of CQ. Four out of 540 patients treated with combination CQ and PQ had a symptomatic recurrence of P. vivax parasitemia within 35 days of treatment initiation, possibly indicating CQ failure. Whole blood total CQ level for one of these four subjects was 95 ng/ml on the day of recurrence. Based on published criteria that delineate CQRPV as a P. vivax parasitemia, either recrudescence or relapse, that appears against CQ blood levels >100 ng/mL, we document the occurrence of a P. vivax strain in Peru that had unusually high tolerance to the synergistic combination therapy of CQ + PQ that normally works quite well.